(untitled) ([Austin], 2004)
The book consists of interactive exercises with feedback, review materials, real-life applications, a student help center and free technical support. Features for the professors: A custom website, custom reports and tracking, community features, test bank and test, free technical support and professor help center
Keywords: Algebra,Trigonometry,Precalculus